1985
DOI: 10.1068/p140685
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Disparity Gradient in Stereo Vision

Abstract: Burt and Julesz experimentally demonstrated that, in addition to Panum's fusional area, a quantity defined by them and named disparity gradient also plays a crucial part in deciding whether the human visual system would be able to fuse the images seen by the left and right eyes. The physical meaning of this quantity remains obscure despite attempts to interpret it in terms of depth gradient. Nevertheless, it has been found to be an effective selector of matches in stereo correspondence algorithms. A proof is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

1988
1988
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 3 publications
2
16
0
Order By: Relevance
“…Disparity gradients at these limiting values indicate the cases where two objects lie on a common line of sight for one eye. It was reported that absolute value of disparity gradient for two dots must be Ͻ1-2 for binocular fusion depending on exact dot parameters (Burt and Julesz 1980;Prazdny 1985;Trivedi and Lloyd 1985). For this reason, we would expect most neurons to be encoding disparity gradient within these limits, if neural encoding of surface slants is constructed in an efficient manner.…”
Section: Spatial Frequency-tuning Testmentioning
confidence: 99%
“…Disparity gradients at these limiting values indicate the cases where two objects lie on a common line of sight for one eye. It was reported that absolute value of disparity gradient for two dots must be Ͻ1-2 for binocular fusion depending on exact dot parameters (Burt and Julesz 1980;Prazdny 1985;Trivedi and Lloyd 1985). For this reason, we would expect most neurons to be encoding disparity gradient within these limits, if neural encoding of surface slants is constructed in an efficient manner.…”
Section: Spatial Frequency-tuning Testmentioning
confidence: 99%
“…al. that a vector field with a d t =1.0 represents a stereo vision field of view that has no occlusion or overlap in the target scene [13]. A value of 2.0 or greater indicates occlusion or other discontinuities.…”
Section: Disparity Gradient Filtering Module: "Flow"mentioning
confidence: 99%
“…5Ronghly speaking, a bound on first differences of disparities. See [Burt & Julesz 1980a, b;Fleck 1988b;Pollard, Mayhew, & Frisby 1985;Trivedi & Lloyd 1985] for details. 6All synthetic stereo pairs shown in this article are generated with the full range of intensity values ([0, 255]) and then degraded to simulate real image conditions.…”
Section: Notesmentioning
confidence: 99%